(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article will analyze the development and development of the state language and national languages in the 21st century. The main focus will be on the question of the rivalization of national languages, their legal status in the now globalizing world. The languages of the world are classified according to their legal status.